2008
DOI: 10.1161/atvbaha.107.151175
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Inhibition Reduces Aortic Ultrasmall Superparamagnetic Iron Oxide Uptake in a Mouse Model of Atherosclerosis

Abstract: Objective-Ultrasmall superparamagnetic iron oxide (USPIO) contrast agents have been used for noninvasive MRI assessment of atherosclerotic plaque inflammation. The purpose of this study was to noninvasively evaluate USPIO uptake in aorta of apoE Ϫ/Ϫ mice and to determine the effects of Angiotensin II (Ang II) infusion and chronic antiinflammatory treatment with a p38 MAPK inhibitor on this uptake. Methods and Results-ApoEϪ/Ϫ mice were administered saline or Ang II (1.44 mg/kg/d) for 21 days. In vivo MRI assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 37 publications
1
72
1
Order By: Relevance
“…The frequency shifts produced by iron-loaded plaques in vivo are not expected to be as strong and localized as in our phantom, mainly due to lower concentration of the contrast agent and the spatial extension of plaques. However, in vivo, images of mice and rabbits model (6,8) showed lumens with dark regions in the vicinity of plaques at relatively moderate gradient echo times, so-called functional stenosis (23), which is illustrated in Fig. 6a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency shifts produced by iron-loaded plaques in vivo are not expected to be as strong and localized as in our phantom, mainly due to lower concentration of the contrast agent and the spatial extension of plaques. However, in vivo, images of mice and rabbits model (6,8) showed lumens with dark regions in the vicinity of plaques at relatively moderate gradient echo times, so-called functional stenosis (23), which is illustrated in Fig. 6a.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they can be identified by signal voids, which are caused by static dephasing induced by the off-resonance field (3). Due to this contrast mechanism, atherosclerotic plaques have been successfully visualized in the aortic vessels of apolipoprotein E knock-out (ApoE À/À) mice (8), hyperlipidemic rabbits (6), and human carotid (9,10) and aortic vessels (11). This work focuses on improving methods for plaque detection using superparamagnetic iron oxide particle/ USPIO contrast agents.…”
mentioning
confidence: 99%
“…To emphasize small concentrations, natural logarithms of the dilution factor (eg, ln(1/20480) for concentration 17.1 nmol Fe/mL) were used as weights in calculating the weighted mean parameters (see Eq. [3] in Appendix C). To calculate the weighted mean flip angle for FISP, the flip angle yielding the most negative CNR saline-CM for each concentration was used.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating USPIOs are primarily phagocytosed by white blood cells of the monocyte/macrophage cell line (2). Therefore, accumulation of USPIOs reflects recruitment of macrophages (or phagocytic activity of macrophages) and is an indication of inflammation (3).…”
mentioning
confidence: 99%
“…1,[3][4][5]9 Available preclinical studies and clinical trials in humans suggest that the optimal time for detecting the MRI signal loss induced in atherosclerotic lesions using dextran-or other polymercoated USPIO (eg, ferumoxtran-10, ferumoxytol, or P904), is 24 to 48 hours after IV administration. [3][4][5][11][12][13] This is clearly not optimal for ensuring a smooth workflow in the routine clinical setting. Several cell culture studies have shown that cellular uptake of citrate-coated iron oxide nanoparticles is faster and quantitatively superior to that of polymer-coated iron oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%